PENDIDIKAN KECAKAPAN HIDUP GENERASI MUDA BUDDHIS SEBAGAI ASET STRATEGIS SUMBER DAYA MANUSIA MASA DEPAN - Puspita Dewi, Metta (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2025)
The younger generation of Buddhists faces vulnerabilities in terms of education, religious identity, and life skills. This study aims to describe how the Pusdiklat Bodhidharma Pusat Semarang (PBPS) manages value-based life skills to develop a talent pipeline for the next generation of Buddhists as strategic assets for the future. This qualitative research uses a case study of PBPS students. Data were collected through interviews, observation, and documentation. Data were analyzed through reduction, presentation, and drawing conclusions using triangulation of sources and techniques. The findings demonstrate 1) planning based on environmental analysis by integrating the potential of foster children and donors; 2) implementation of life skills, including personal skills (practicing noble morals, discipline, and simplicity); social skills (teamwork and conflict management); academic skills (wall magazines, devotional services, and Sunday school); vocational skills (event organizing, agriculture, wedang uwuh entrepreneurship, and crafts); and 3) control through value-based evaluation. The findings broaden the perspective of skills into the process of forming value-based human and social capital. Practical implications of formulating a SAFE (sequenced, active, focused, and explicit) program design, senior mentoring of juniors, digital self-regulation, and ethical entrepreneurship relevant to the concept of right livelihood (sammaajiva).